The Vegetation of Asirgarh Hills (Madhya Pradesh) - Maheshwari, J. K. (Indian Forester, 1960)
This paper deals with the vegetation of Asirgarh, a famous hill fort in Madhya Pradesh. There had never been a systematic study of the flora of these hills. The present work was, therefore, undertaken by the author during the years 1958 and 1959, and is confined mainly to the study of trees, shrubs and climbers inhabiting the hills. The forest vegetation is of the dry deciduous type. It is, in general, a tropical thorn forest, represented by the scrub jungles. However, in protected and inaccessible parts of the hills; mixed deciduous forests of salai (Boswellia serrata Roxb.) and anjan, (Hardwickia binata Roxb.) are frequently met with. Considerable biotic interference as well as intense grazing has destroyed vast stretches of tree vegetation, so that in some places the hills are fast heading towards denudation. A total number of 145 species of plants, is reported from the hills.